Lecture introduction : Bridging students’ background knowledge with new lecture content - Yeo, Jacinta Jiin-Yih; Ting, Su Hie (AJTLHE, 2012)
This study examined the use of lecture introductions for bridging students’ background knowledge with new lecture content. The specific aspects studied were the organisational structure of the lecture introduction, and the use of questions and pronouns to engage students’ thinking on the content of the lecture. A case study was conducted at a Malaysian university, involving lecturers from seven faculties. Forty-seven lecture introductions were audio-taped and transcribed. Analysis of the organisational structure of lecture introductions based on Schuck (1970) and Davies (1981) revealed that activating students’ prior knowledge was the main component of the lecture introduction, but lecturers tended to state aims and objective of the lecture; point out importance of mastering the knowledge; and make announcements and give instructions before proceeding to the body of the lecture. To engage students in a communicative discussion, the lecturers were found to use the second-person pronoun “we” more frequently than “I” and “you” to include students in the intellectual discourse. Questions were also extensively used to activate students background knowledge and establish a common knowledge base, particularly display questions but they were not effective in generating lecturer-student interaction on the subject matter due to the students’ passive response